The factors affecting the rupiah exchange rate in Indonesia - Nadya Carissa; Rifki Khoirudin (Department of Development Economics, Universitas Sriwijaya, 2020)
This study to determine the money supply, interest rates, inflation, and imports toward rupiah exchange rates. The analysis method in this study used a quantitative approach that applies multiple regression models. Data used secondary data in the form of time series during the period of August 2016 until June 2019. The finding's results show that jointly money supply, interest rates, inflation, and imports have a significant effect on the rupiah exchange rate. While partially, the variable of money supply, interest rates, and imports has a positive and significant effect on the rupiah exchange rate. But the inflation rate has an insignificant effect on the Rupiah exchange rate. From the results of this study the government is expected to control the money supply and maintain the balance of payments by minimizing the amount of imports.